Pembelajaran SKI di Madrasah Tsanawiyah Darul Ilmi - Nasution, Abdul Gani Jamora; ‘Arif, Muhammad; Alwi, Muhammad Fiqri; Khairani, Aulia; Nugraha, Mhd Nuryansyah; Hasanah, Nur Aripa (MASALIQ, 2023)
The History of Islamic Culture is a very important lesson for students to learn because it is one part of Islamic Religious Education subjects which is directed at preparing students to know, understand, live the History of Islamic Culture, which then becomes the basis of their way of life through guidance activities. , teaching, training, use of experience and habituation. SKI Madrasah Tsanawiyah subjects include: History of the Umayyad, Abbasid and al-Ayubiyah dynasties. Another thing that is very basic lies in the ability to explore values, meanings, axioms, compassion/wisdom, propositions and theories from existing historical facts. In the subject of Islamic Cultural History, in reality, students are less interested. The research location was at Madrasah Tsanawiyah Darul Ilmi Batang Quiz related to the learning process, obstacles and solutions to learning obstacles of Islamic Cultural History. The method we use is a descriptive qualitative method. The objects we examined were students and teachers at the school. From the results of the research that we obtained, the implementation of SKI learning had gone well according to the contents of the lesson plan made by the SKI teacher. However, there were several obstacles that occurred during the ski learning process, namely other class students were in class when learning was taking place, students were busy, students were drawing during learning, students did not bring packages or modules, students were eating and drinking while learning was taking place, and so forth. In addition, the teacher's efforts in these obstacles are by reprimanding him and asking the student to enter the class, remaining calm and giving the task to the student, admonishing and returning their attention to the lesson by ordering them to read, by asking the reason students don't bring packages or module when students do not bring the module (package), and several other solutions.